The Influence of Initial Ability and Critical Thinking on Science Learning Outcomes through RADEC-Based Comic Media - Raudhotul Jannah; Risda Amini; Muhammadi Muhammadi; Desyandri Desyandri (Postgraduate, University of Mataram, 2025)
This study aims to analyze the influence of initial abilities and critical thinking on learning outcomes through RADEC-based comic media for fourth grade elementary school students. The focus of the study was to determine the extent to which initial abilities and critical thinking affect student learning outcomes. The research method used was quasi-experimental with a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class using RADEC-based comic media and the control class using conventional learning methods. The research instruments included initial ability tests, critical thinking tests, and learning outcome tests. Data were analyzed using the Two-Way ANOVA statistical technique to test the effect of initial abilities and critical thinking on learning outcomes, and the Independent Samples T-Test to compare differences in learning outcomes between the experimental and control classes. The results showed that: students' initial abilities had a significant effect on learning outcomes through RADEC-based comic media; critical thinking had a significant effect on learning outcomes; the interaction between initial abilities and critical thinking did not have a significant effect on learning outcomes. The practical implications of this study are the importance of considering students' initial abilities and critical thinking in designing learning strategies, as well as the use of RADEC-based comic media as an effective learning alternative in Elementary Schools.